Ответы и объяснения

2014-03-20T09:41:48+00:00
№1(-0,5)^2*4/3-5+1 2/3 = 0.25*4/3-5+1 2/3 = 1/4*4*3-5+ 1 2/3 = 1/3 - 5 + 1 2/3 = 2-5 = -3 Ответ: -3   №2   3(x-2)-4(8-x) >=9(x-2)    3x-6-32+4x >= 9x-18     3x-6-32+4x-9x+18 >=0    -2x-20 >=0     -2x>=20    x<=-10x   Э (-∞; -10] (вместо "э" знак "принадлежит")  Ответ: (-∞; -10].№3    2x/ (x^2-4) - 1/(x-2)        (x^2-4) = (x+2)(x-2);      домножить  1/(x-2) на (x+2) :
2x/ (x^2-4) - (x+2)/(x^2-4)       (2x-x-2) / (x^2-4) = (x-2)/(x^2-4) = (x-2)/(x-2)*(x+2) = 1/(x+2)  = 1/(-1.5+2) = 1/0.5 = 2    Ответ: 2